2009
DOI: 10.5751/ace-00326-040204
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Rangewide Mitochondrial Introgression Indicates Substantial Cryptic Hybridization in the Golden-winged Warbler (Vermivora chrysoptera)

Abstract: Widespread population declines of the Golden-winged Warbler (Vermivora chrysoptera) are thought to be due in part to hybridization with the expanding Blue-winged Warbler (V. pinus), which predictably replaces Golden-winged Warblers at breeding sites in which the two species come into contact. However, the mechanism by which this replacement occurs remains unresolved. Recent genetic work has indicated that, even in areas where the two species have been in contact for a short period, introgression of Blue-winged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 17 publications
0
44
1
Order By: Relevance
“…This is likely because of the fact that we focused our surveys in areas that had a combination of extensive forest cover (mean = 84.2% within 1 km) at higher elevation (mean = 570 m, range = 275-946 m). However, we must caution that cryptic hybridization is likely to occur in the Golden-winged Warbler population we studied (Vallender et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely because of the fact that we focused our surveys in areas that had a combination of extensive forest cover (mean = 84.2% within 1 km) at higher elevation (mean = 570 m, range = 275-946 m). However, we must caution that cryptic hybridization is likely to occur in the Golden-winged Warbler population we studied (Vallender et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, once the point count was complete, each observer used playback of a Golden-winged Warbler song until achieving positive visual confirmation of each individual by plumage characteristics, e.g., black throat, and behavior, e.g., singing. However, it should be noted that even with the confirmation of a phenotypic Golden-winged Warbler, there likely exists cryptic hybridization in the Golden-winged Warbler population we studied (Vallender et al 2009). …”
Section: Bird Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Fowlds (2010) studied GWWAs and BWWAs in a variety of habitat types in central Wisconsin and noted densities of 0.12 (1.3) (SE) to 0.31 (1.2) and 0.06 (1.3) to 0.09 (1.3) per ha for GWWAs and BWWAs respectively. Mitochondrial DNA analysis indi- v www.esajournals.org cates bi-directional introgression in our study area and among the highest introgression rates ever reported for both species (Vallender et al 2009; approximately 15% for GWWAs and 25% for BWWAs).…”
Section: Study Areamentioning
confidence: 99%
“…Vallender et al (2007) reported a high rate of GWWA intraspecies extra pair matings and suggested this might also be common with the BWWA. Hybridization between the two species has received extensive phenotypic (Parkes 1951, Gill 1980, 1987, mitochondrial DNA (mtDNA) (Gill 1997, Shapiro et al 2004, Dabrowski et al 2005, and nuclear DNA ) study indicating genetic introgression is bi-directional (Shapiro et al 2004, Dabrowski et al 2005) and extensive (Vallender et al 2009). Based on the mtDNA studies, the species' genomes overlap by 95.1-97.0% (Gill 1997, Shapiro et al 2004, Dabrowski et al 2005 and split from an ancestral species approximately 1.5 million years before present (Gill 2004).…”
Section: Introductionmentioning
confidence: 99%